ANALISIS PENENTUAN JUMLAH TENAGA KERJA BERDASARKAN BEBAN KERJA PADA IKM PENGRAJIN BANTAL ABC - Ritonga, Robhyano; Zetli, Sri (LPPM Universitas Putera Batam, 2026)
IKM pillow maker ABC is a business that produces various types of pillows, mattresses, and sofas using different fillings such as dacron, cotton, and foam. The pillow production station currently employs 6 workers: 1 worker for cotton grinding, feeding cotton into the machine, and packaging, 2 workers for filling cotton into the pillows, 2 workers for sewing, and 1 worker for final inspection. Based on observations, one of the main problems identified is that the demand level is significantly higher than the average daily production capacity. As a result, the current workforce is unable to complete production tasks on time, leading to delays in meeting customer orders. To address this issue, it is necessary to calculate the workload and determine the optimal number of workers required to achieve the production target. This study applies Workload Analysis and Workforce Analysis to determine the ideal workforce allocation. The results indicate that the optimal number of workers needed includes: 1 worker for cotton feeding and grinding, 10 workers for filling cotton into pillows, 11 workers for sewing, 3 workers for quality inspection, and 3 workers for packaging. By increasing the number of workers in these key areas, the company is expected to significantly improve its productivity and meet customer demand more effectively.